1998
DOI: 10.1021/js980060r
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Delivery of Nanoparticles of Insoluble, Iodinated CT x-ray coNtrast Agents to Lung Draining Lymph Nodes in Dogs

Abstract: Lung cancer continues to be a leading cause of death around the world. Staging of this disease is critically dependent upon the involvement or noninvolvement of the lymph nodes which drain the region of lung containing the lesion/tumor. Palpation, unenhanced CT, and lymph node excision (i.e., mediastinectomy) are currently used to ascertain the status of these regional draining lymph nodes. The work reported herein details the first efforts toward the pulmonary instillation of iodinated nanoparticles for contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Research essentially focuses [213,214] on the incorporation of iodinated organic compounds into NPs, with designs ranging from emulsions, [215][216][217][218] liposomes, [214,[219][220][221][222][223] and lipoproteins, [224,225] to insoluble nano objects, [214,[226][227][228] and polymeric NPs, [215,[229][230][231][232][233]; many of them have been successfully applied in vivo [28,56]. The purpose of these nanomaterials is to locally increase iodine concentrations, Some multimodal nanoparticles were doped with an iodinated compound and used to enhance X-ray contrast [216,224,234,235] as discussed in later on in the review.…”
Section: Iodinated Nanoparticlesmentioning
confidence: 99%
“…Research essentially focuses [213,214] on the incorporation of iodinated organic compounds into NPs, with designs ranging from emulsions, [215][216][217][218] liposomes, [214,[219][220][221][222][223] and lipoproteins, [224,225] to insoluble nano objects, [214,[226][227][228] and polymeric NPs, [215,[229][230][231][232][233]; many of them have been successfully applied in vivo [28,56]. The purpose of these nanomaterials is to locally increase iodine concentrations, Some multimodal nanoparticles were doped with an iodinated compound and used to enhance X-ray contrast [216,224,234,235] as discussed in later on in the review.…”
Section: Iodinated Nanoparticlesmentioning
confidence: 99%
“…74,76 Further, alveolar clearance of drug particles up to a certain diameter (200 nm) involves the lymphatic system. 71,78,79 This renders drug targeting with SLNs feasible, and several studies have been done involving delivery of SLNs in patients with lung cancer via nebulization and gene therapy. 72,80 Videira et al formulated an SLNs system incorporating paclitaxel, which is widely used in the treatment of non-small cell lung cancer.…”
Section: Pulmonary Route For Lymphatic Delivery Of Slnsmentioning
confidence: 99%
“…Uptake of SLNs into the lymphatic system was demonstrated earlier by Videira et al using radiolabeled SLNs whereas other researchers used a computed tomography contrast agent. 71,79 Both studies demonstrated that biodistribution of SLNs occurs primarily via the lymphatic system rather than by the blood circulation. Thus, specific delivery of cytotoxic drugs via inhalation using SLNs could be a promising option for chemotherapy in the future.…”
Section: Pulmonary Route For Lymphatic Delivery Of Slnsmentioning
confidence: 99%
“…Risk assessment of nanomaterials is, however, mainly done using animals, like rats (Kapp et al, 2004;Geiser et al, 2005;Kuempel et al, 2006), mice (Vaughn et al, 2006), cats (Bice et al, 2000), as well as dogs (McIntire et al, 1998;Bice et al, 2000;Wellenius et al, 2003).…”
Section: Particle Incubationmentioning
confidence: 99%